Comparison study between Propofol plus Remifentanyl versus Propofol plus Dexmedetomidine in maintaining “Asleep Awake Asleep” Procedure During Awake Craniotomy After Scalp Block (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Awake craniotomy is a neurosurgical technique in which pharmacological agents are used to modulate patient consciousness in order to facilitate optimal tumor resection or functional mapping while maintaining patient comfort, but allowing for intraoperative neurological assessment; thus, improving the safety and efficacy of tumor resections located in eloquent brain regions, The "asleep-awake-asleep" method necessitates effective sedation protocols that are aimed at achieving adequate patient comfort, patient cooperation and minimal side effects.Objectives: The objective of this study was to compare the efficacy, safety and clinical outcomes of two anaesthetic regimens, Propofol with Remifentanyl and Propofol with Dexmedetomidine in maintaining the asleep-awake-asleep (AAA) during awake craniotomy.Methodology: A total number of 60 patients presented with brain tumour who were operated in the Department of Neurosurgery of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh was included in this current study. This is the largest tertiary care center and the only national referral center hospital in Bangladesh. Data on demography and events from January 2021 to December 2024 for a period of three (03) years. Adult Bangladeshi males and females with age group of 18 to 50 years were included as study population. Selected patients were divided into two group with ASA grade I and II of which patients in group A were treated with Propofol plus Remifentanyl and the group B treated with Propofol plus Dexmedetomidine conservatively in maintaining “Asleep Awake Asleep” procedure during awake craniotomy after scalp block.Results: A total number of 60 patients presented with brain tumour who were operated in the Department of Neurosurgery of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh was included in current study.  In this study Group A Propofol with Remifentanyl demonstrated superior control heart rate (75 ± 7) compared with Group B Propofol with Dexmedetomidine (82 ± 9). In the sleeping phases, patients in the Propofol with Dexmedetomidine group had a significantly lower respiratory rate (10±2, p = 0.02) than those in the Propofol with Remifentanyl group (12±2, p = 0.01). However, the incidence of desaturation (SpO₂ < 95%) was higher in the Propofol with Dexmedetomidine group than in the Propofol with Remifentanyl group (13% vs. 3%, p = 0.04). Patients who were in the Propofol with Remifentanyl group expressed more pleasure than those in the Propofol with Dexmedetomidine group (9.2 ± 0.8 vs. 8.5 ± 1.1, p = 0.02). Compared to the Propofol with Dexmedetomidine group, patients in the Propofol with Remifentanyl group were able to follow instructions more quickly (10.5 ± 2.1 minutes vs. 15.3 ± 2.5 minutes, p = 0.001).Conclusion: In conclusion both combinations worked well to keep the asleep-awake-asleep protocol in place, but Propofol with Remifentanyl is the better option for awake craniotomy because it offers better hemodynamic stability, smoother transitions, and fewer adverse events. Remifentanil also offers superior analgesia and a quicker recovery.Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):68-74